Prolonged visual fixation as a surrogate marker of cholinergic deficit in Parkinson's disease: A 2-year follow-up study. (December 2020) - Wong, Oscar WH.; Chan, Anne; Wong, Adrian; Lau, Claire KY.; Yeung, Jonas HM.; Mok, Vincent; Chan, Sandra
Abstract: Introduction: The search for biomarkers of cognitive impairment in Parkinson's disease is driven by the potential clinical applications in disease prognostication. Various eye tracking studies on cognitive functions in Parkinson's disease suggest a promising role of eye movement parameters as a biomarker for cognitive decline but the clinical utility has not been validated in longitudinal studies. The present study aims to investigate the longitudinal progression of eye fixation duration in a visual search task and its correlation with domain-specific cognitive impairment. Method: This is a 2-year follow-up study on a group of non-demented Parkinson's disease patients, with baseline eye movement metrics and multi-domain cognitive functions measured, to assess the association between domain-specific cognitive impairment and progression of visual fixation duration. Results: A total of 49 from the original 62 non-demented Parkinson's disease patients were re-examined at a 2-year follow-up. 15 cases (31%) were classified as having mild cognitive impairment. Visual fixation duration was significantly prolonged after 2 years. Using repeated measures ANOVA, impairment in semantic verbal fluency, visual and verbal recognition memory and orienting function of attention had a significant effect on prolonging visual fixation over time. Conclusion: Correlation between prolonged visual fixation and multiple domains of cognitive impairment related to cholinergic dysfunction in repeated measures over two years provides preliminary evidence for the eye tracking paradigm as a surrogate marker for cholinergic deficit in Parkinson's disease. The clinical utility in terms of disease prognostication is yet to be confirmed in prospective longitudinal studies with longer follow-up periods. Highlights: Cholinergic deficit is a key mediator of clinical outcome in Parkinson's disease. Visual fixation duration is associated with cholinergic-based cognitive functions. The associations appear to have stability over 2 years and are specific in nature. Measurement of fixation duration can be a potential marker for cholinergic deficit. Its association with broader spectrum of cholinergic functioning is to be explored.